GESTURE TANGAN DALAM KOMUNIKASI ORANG JEPANG - Suraya, Kiki; Hermandra, Hermandra; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research discuses about Hand’s Gesture in Japanese People’s Communication. On this research, writer using descriptive qualitative method with theory semiotic triangle by Pierce (1839-1914) and theory speaking by Hymes (1962) for speech component. The background of this study is hand’s gesture have many variations in the use of body language learning. The same hand movements sometimes have similarities and differences in the intentions conveyed from the sender and recipient of the message. After collecting data in Lovely Complex and Tada Kimi wo Aishiteru film, writer found 3 types of teburi, it’s finger movements, arm movements, wrist and palm movements. 3 kinds of finger movements, 3 kinds of arm movements, 6 kinds of wrist and palm movements. There are 12 types because Yubi wo Sasu gesture and Watashi gesture have the same movements. Okama gesture and Warau gesture have the same movements too, but the position is different. After analized, hand’s gesture is used to replace verbal messages, emphasize verbal messages, repeat verbal messages, deny verbal messages and complete verbal messages.Key Words: Nonverbal communication, gesture, teburi.